Nexus of imports in influencing exports, domestic demand and services amongst ASEAN-5 countries - Dass, Anthony (2018)
There has been growing concern that trade-dependent ASEAN-5 (Indonesia, Malaysia, Philippines, Singapore and Thailand) countries are losing their grip as trading nations due to the weaker contribution of net exports to Gross Domestic Product (GDP) with domestic demand contribution to GDP improving. This casts doubts on the Export-Led Growth Strategy (ELGS) with the growing perception that the Domestic Demand-Led Growth Strategy (DDLGS) is gaining prominence. The main aim of this study is to determine the connection between import and export components on private consumption, public consumption, gross fixed capital formation, exports, imports and services. Autoregressive Distributive Lag (ARDL) and Pedroni’s Panel cointegration techniques were applied to the data covered from the year 1996 to 2015. The results explain that import components significantly influence domestic demand variables and exports. The results also support that the domestic demand contribution to GDP is being overestimated while net exports contribution to GDP is underestimated due to the impact of imported components. At the same time, the results unveil a significant and positive impact of imported components on services which indicate the overestimating services contribution to GDP. The results demonstrate a significant positive impact of export components on domestic demand and net exports. Finally, the estimates of export components reveal positive and significant impact on the services sector. The main policy implication that can be deduced is that both import and export components significantly influence domestic demand, net exports and services. These components benefit from the ASEAN-5 integration and from their respective country’s policies. The authorities should design their policies by taking into consideration the impact of these components and regional integration to ensure they benefit in a more effective and efficient manner.